2021
DOI: 10.1038/s41467-021-23085-0
|View full text |Cite
|
Sign up to set email alerts
|

NBR1 is a critical step in the repression of thermogenesis of p62-deficient adipocytes through PPARγ

Abstract: Activation of non-shivering thermogenesis is considered a promising approach to lower body weight in obesity. p62 deficiency in adipocytes reduces systemic energy expenditure but its role in sustaining mitochondrial function and thermogenesis remains unresolved. NBR1 shares a remarkable structural similarity with p62 and can interact with p62 through their respective PB1 domains. However, the physiological relevance of NBR1 in metabolism, as compared to that of p62, was not clear. Here we show that whole-body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In addition to its role in autophagy, p62 serves as a signaling hub that participates in multiple pathways, but most notably, p62 regulates beige and brown adipocyte formation. Knockout of p62 in adipose tissue results in obesity, glucose intolerance, and reduced energy expenditure, effects attributed to reductions in brown and beige adipose tissue thermogenesis (Fischer et al, 2020; Huang et al, 2021; Muller et al, 2013). Mechanistically, p62 directs phospho-ATF2 to promoters of thermogenic genes and also functions as co-activator of PPARγ (Fischer et al, 2020; Huang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its role in autophagy, p62 serves as a signaling hub that participates in multiple pathways, but most notably, p62 regulates beige and brown adipocyte formation. Knockout of p62 in adipose tissue results in obesity, glucose intolerance, and reduced energy expenditure, effects attributed to reductions in brown and beige adipose tissue thermogenesis (Fischer et al, 2020; Huang et al, 2021; Muller et al, 2013). Mechanistically, p62 directs phospho-ATF2 to promoters of thermogenic genes and also functions as co-activator of PPARγ (Fischer et al, 2020; Huang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Knockout of p62 in adipose tissue results in obesity, glucose intolerance, and reduced energy expenditure, effects attributed to reductions in brown and beige adipose tissue thermogenesis (Fischer et al, 2020; Huang et al, 2021; Muller et al, 2013). Mechanistically, p62 directs phospho-ATF2 to promoters of thermogenic genes and also functions as co-activator of PPARγ (Fischer et al, 2020; Huang et al, 2021). It is tempting to speculate that FasnKO-mediated increases in adipose tissue p62 as a result of autophagy dysfunction regulate the beiging and metabolic improvements observed in these mice, but FasnKO in vitro does not upregulate Ucp1 under our experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that p62 plays a significant role in the regulation of thermogenesis in BAT. A recent paper has demonstrated that NBR1 is required for the repression of adaptive thermogenesis via decreasing the activity of PPARγ in BAT of p62-deficient mice; thereby, the inhibitory role of NBR1 in thermogenesis in the presence of p62 inactivation was identified [ 87 ]. Based on these studies, further investigations may reveal the role of p62 and NBR1 in the thermogenesis of human brown and beige adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is characterized by increased mass in the adipose tissue, which is linked to the persistent activation of inflammatory pathways in both adipocytes and macrophages living in or invading the adipose tissues [ 10–12 ]. A previous study has revealed that the adipocyte’s p62 is a critical regulator of energy balance and adiposity in vivo [ 13 ]. Moreover, Trayhurn P. demonstrated that adipose hypoxia might be a causative factor for adipose dysfunction in obesity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%